ANALISIS PENGUKURAN KINERJA PERUSAHAAN DENGAN PENDEKATAN BALANCED SCORECARD (Studi kasus: PerusahanTelekomunikasi di Padang) - Rizki Alfi; Rudianto Rudianto (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
Balanced Scorecard (BSC) is an organizational performance appraisal model that emphasizes the measurement of financial and non-financial aspects as well as the result of a top-down process based on the mission and strategy of an organization. Performance appraisals with the Balanced Scorecard are translated into four perspectives: (1) Financial Perspective, (2) Customer Perspective, (3) Internal Business Perspective, and (4) Learning and Growth Perspective. The research method is identification of objective strategy and Key Performance Indicator (KPI), structuring KPI, weighting KPI using Analytical Hierarchy Process (AHP) method. The AHP method is the ability to accommodate interconnectedness between criteria or alternatives. Where there are 7 Objective Strategies and 10 KPIs translated within the framework of the AHP Strategy. This study discusses the measurement of corporate performance with the aim to improve performance (performance) by knowing the weight of each perspective, objective strategy and KPI. Based on the results of data processing obtained weight of each perspective are: Financial Perspectives 0.26, Customer Perspective 0.29, Internal Business Perspective 0.20, and Growing Perspective 0.26. From the results of the research shows that the weight of the Perspective of the Customer is greater than the other three perspectives.